1998
DOI: 10.2337/diabetes.47.11.1676
|View full text |Cite
|
Sign up to set email alerts
|

Tyrosine phosphatase inhibitors, vanadate and pervanadate, stimulate glucose transport and GLUT translocation in muscle cells by a mechanism independent of phosphatidylinositol 3-kinase and protein kinase C.

Abstract: Vanadate and pervanadate (pV) are protein tyrosine phosphatase (PTP) inhibitors that mimic insulin to stimulate glucose transport. To determine whether phosphatidylinositol (PI) 3-kinase is required for vanadate and pV, as it is for insulin, cultured L6 myotubes were treated with vanadate and pV. The two compounds stimulated glucose transport to levels similar to those stimulated by insulin; however, while PI 3-kinase activity and the increase in the lipid products PI 3,4-bisphosphate and PI 3,4,5-trisphosphat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

11
80
2

Year Published

1999
1999
2004
2004

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 105 publications
(93 citation statements)
references
References 63 publications
11
80
2
Order By: Relevance
“…Recent data suggest that this enzyme modulates the intrinsic activity of GLUT4 and, thus, the stimulation of glucose uptake by insulin in skeletal muscle (36) and 3T3-L1 adipocytes (34,40). In contrast, vanadate-mediated glucose uptake has been shown to be independent of p38 MAPK activation (43). Together, these results suggest that acute vanadate stimulation of glucose uptake occurs through the activation of a different signaling pathway than insulin.…”
mentioning
confidence: 47%
See 3 more Smart Citations
“…Recent data suggest that this enzyme modulates the intrinsic activity of GLUT4 and, thus, the stimulation of glucose uptake by insulin in skeletal muscle (36) and 3T3-L1 adipocytes (34,40). In contrast, vanadate-mediated glucose uptake has been shown to be independent of p38 MAPK activation (43). Together, these results suggest that acute vanadate stimulation of glucose uptake occurs through the activation of a different signaling pathway than insulin.…”
mentioning
confidence: 47%
“…Acute activation of glucose transport by millimolar concentrations of vanadate has been observed in many tissues, including adipocytes, cardiomyocytes, and skeletal muscle (19,20,31,41,43). However, chronic vanadate exposure could stimulate glucose uptake at different concentrations from the one observed for acute exposure.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Surprisingly, there is little evidence of any effect of agents being capable of stimulating glucose transport on the activation of Akt1. A recent report showed that vanadium compounds activated Akt1 and this activation was inhibited by wortmannin [54]. This is, however, inconsequential for glucose transport because the stimulation of glucose transport by vanadate is wortmannin-insensitive [55].…”
Section: Discussionmentioning
confidence: 99%